Governing anthropogenic assets for nature’s contributions to people in forests: a policy document analysis - Isaac, Roman; Hofmann, Johanna; Koegst, Jana; Schleyer, Christian; Martín-López, Berta (Environmental science & policy, 2024)
Forests support human wellbeing by providing multiple nature’s contributions to people (NCP). These are derived from an interplay of both natural and anthropogenic assets, which is a process known as NCP co-production. Like forests and NCP, anthropogenic assets are subject to modes of governance operating across multiple levels, in which policies are a central tool for executing formal governance. Here, we conduct a policy document analysis to investigate how policies refer to both the anthropogenic assets involved in NCP co-production and the modes of governance affecting these, i.e., hierarchical, scientific-technical, (adaptive)-collaborative governance, and the governing of strategic behaviour. The policy document analysis focuses on forestry and biodiversity conservation policies spanning across multiple governance levels, from the local level – two Biosphere Reserves and one National Park in Germany – to the supra-national level of the European Union. We find that policies predominantly address material and regulating NCP and refer to hierarchical and scientific-technical governance. Based on a redundancy analysis, we identify six archetypes of governance of NCP and the anthropogenic assets underpinning their co-production: (1) the governing of strategic behaviour for regulating NCP, (2) governing habitat management for experiences in nature, (3) governing habitat management for pest control, (4) collaborative governance for timber, (5) local governance for experiences in nature, and (6) promoting knowledge for habitat protection. Our analysis thereby unveils how policies intend to govern anthropogenic capitals related to the co-production of specific forest NCP. The findings, including the six archetypes, can support policymakers in designing policies across governance levels.